2008
DOI: 10.1002/pam.20379
|View full text |Cite
|
Sign up to set email alerts
|

Minimum wages and the economic well‐being of single mothers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 60 publications
(64 reference statements)
2
54
1
3
Order By: Relevance
“…On net, Neumark and Wascher (2002) find that the families of low-skilled workers are no better off and may be made worse off by minimum wage hikes. Sabia (2008) finds a similar result for lesseducated single mothers. A second approach, taken by Card and Krueger (1995) and Burkhauser and Sabia (2007), estimates the effect of state minimum wage increases on state poverty rates.…”
Section: Poverty Effects Of Minimum Wage Increasessupporting
confidence: 56%
See 4 more Smart Citations
“…On net, Neumark and Wascher (2002) find that the families of low-skilled workers are no better off and may be made worse off by minimum wage hikes. Sabia (2008) finds a similar result for lesseducated single mothers. A second approach, taken by Card and Krueger (1995) and Burkhauser and Sabia (2007), estimates the effect of state minimum wage increases on state poverty rates.…”
Section: Poverty Effects Of Minimum Wage Increasessupporting
confidence: 56%
“…But this finding is far from definitive. Other studies that have examined low-skilled workers across sectors have found evidence of adverse employment and welfare take-up effects even after controlling for unmeasured state trends (Page, Spetz, and Millar 2005;Sabia 2008;Sabia and Burkhauser 2008).…”
Section: Employment and Hours Worked Effects Of Minimum Wage Increasesmentioning
confidence: 99%
See 3 more Smart Citations